EFEKTIVITAS SISTEM AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DI KABUPATEN SUMBA TIMUR - Ferdelince Lunga Nani; Hyronimus Rowa; Ani Martini (Institut Pemerintahan Dalam Negeri, 2021)
This research is motivated by a change in the perspective of the administration of the bureaucracy from work orientation to a results-oriented bureaucracy with an emphasis on performance accountability. This study aims to determine and analyze the effectiveness of the Performance Accountability System of Government Agencies in increasing the accountability of local government in East Sumba Regency. The research design use descriptive qualitative with data collection techniques through interviews, documentation and observation. The selection of informants was done based on purposive sampling technique. The theory used is the theory of effectiveness according to Duncan, namely the achievement of goals, integration and adaptation. The results of the study indicate that the implementation of the Government Performance Accountability System in East Sumba Regency has not been effective, as shown in the following three dimensions: 1) the achievement of the objectives is not fully met in terms of timeliness and targets. which is the target in the performance indicators set out in the document; 2) Integration, from the process and procedure of socialization that has not been running as expected, namely from the quantity of activities and results to be achieved, the lack of response from regional officials and the lack of competence of the organizers in addition, consensus development occurs without performance evaluation; 3) Adaptation of the implementation of this system from the availability of adequate supporting infrastructure but in terms of the use of information technology there is no such thing and increasing the capacity of resources, it is not optimal. Keyword: Effectiveness, The Government Agency Performance Accountability System, Local Government